2019
DOI: 10.3390/met9090931
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Processing Method on the Properties of Ti-23 at.% Mo Alloy

Abstract: In this paper, binary β type Ti-23 at.% Mo alloys were obtained by arc melting as well as by mechanical alloying and powder metallurgical process with cold powder compaction and sintering or, interchangeably, hot pressing. The influence of the synthesis method on the microstructure and properties of bulk alloys were studied. The produced materials were characterized by an X-ray diffraction technique, scanning electron microscopy and chemical composition determination. Young’s modulus was evaluated with nanoind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 51 publications
(78 reference statements)
0
10
0
2
Order By: Relevance
“…The aim of the current study is directed at improving the physicochemical and mechanical properties as well as biocompatibility of Ti-based systems through crystal structure evolution (α → β) and new microstructure formation (micro → nano or ultrafine) via its chemical composition modification and processing method, respectively [ 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. β-type titanium alloys are interesting biomaterials for innovative implantable medical devices.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The aim of the current study is directed at improving the physicochemical and mechanical properties as well as biocompatibility of Ti-based systems through crystal structure evolution (α → β) and new microstructure formation (micro → nano or ultrafine) via its chemical composition modification and processing method, respectively [ 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. β-type titanium alloys are interesting biomaterials for innovative implantable medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…β-type titanium alloys are interesting biomaterials for innovative implantable medical devices. Recently studies on TiMo, TiNb, TiZrNb, TiNbHf, TiNbZrTa, TiNbZrTaSiFe have confirmed their interesting properties for future application in medicine [ 9 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. It is important to note, that the cytotoxicity of Mo, Zr, and Nb is lower than that for commercial purity Ti [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations